2005
DOI: 10.1007/s10529-005-0984-x
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of ?-fructofuranosidase from Aspergillus japonicus on chitosan using tris(hydroxymethyl)phosphine or glutaraldehyde as a coupling agent

Abstract: A partially purified beta-fructofuranosidase from Aspergillus japonicus was covalently immobilized on to chitosan beads using either glutaraldehyde or tris(hydroxymethyl)phosphine (THP) as a coupling agent. Compared with the glutaraldehyde-immobilized and the free enzyme, the THP-immobilized enzyme had the highest thermal stability with 78% activity retained after 12 days at 37 degrees C. The THP-immobilized enzyme also had higher reusability than that immobilized by glutaraldehyde, 75% activity was retained a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…A previous study showed the use of THP as a coupling agent retained 20% more residual activity than the use of glutaraldehyde 9. Therefore, in this work, we immobilized β‐galactosidase on to chitosan using THP as a coupling agent to produce GOS from lactose.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed the use of THP as a coupling agent retained 20% more residual activity than the use of glutaraldehyde 9. Therefore, in this work, we immobilized β‐galactosidase on to chitosan using THP as a coupling agent to produce GOS from lactose.…”
Section: Introductionmentioning
confidence: 99%
“…Fructofuranosidases with fructosyltransferase activity can be used to produce fructooligosaccharides (FOS), as 1-kestose and 1-nystose, prebiotic substances that have important functional properties (Toledo et al 2004;Maiorano et al 2008). Microorganisms have been used to produce these enzymes, especially filamentous fungi such as Aspergillus niger (Rubio and Navarro, 2006), Aspergillus japonicus (Cheng et al 2005), Aspergillus ochraceus (Guimarães et al 2007), Aspergillus niveus (Guimarães et al 2009) and Cladosporium cladosporioides (Almeida et al 2005), among others. The production of β-Dfructofuranosidase by fungi is conducted under Submerged Fermentation (SbmF) or under Solid State Fermentation (SSF) (Romero-Gómez et al 2000;Aranda et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [15] have made chitosan-ZrO 2 composite beads by adding ZrO 2 powders to chitosan/acetic acid slurry. Cheng et al [16] have used tris(hydroxymethyl) phosphine (THP) instead of glutaraldehyde (GA) as a coupling agent to prepare THP-activated chitosan beads. Chiou et al have developed two agents to treat chitosan: one is carbodiimide used for activating the hydroxyl groups of chitosan [17], and the other is genipin, a natural cross-linker of plant origin, used for chitosan cross-linking [13].…”
Section: Introductionmentioning
confidence: 99%